(untitled) (Bangladesh Journal of Child Health, 2016)
Background: Newborns with Hypoxic Ischemic Encephalopathy (HIE) are at risk of neuro-developmental disabilities. Early identification of their neuro-developmental impairments (NDI), immediate intervention and reassessment might be a useful method to measure and prevent major disability. This study was performed to identify impairment in different developmental domains among the babies admitted with moderate to severe degree HIE, and evaluate their outcomes after intervention with developmental therapy and stimulation. Methodology: The exploratory case control study was conducted during April 2008 till February 2012. We enrolled 81 full-term babies admitted to the special care neonate unite with HIE as case. The control group included age and sex matched 81 babies who did not have HIE. Neurodevelopmental assessment was performed using age specific rapid neurodevelopmental assessment tool (RNDA) by trained developmental therapists (DT). Intervention with developmental therapy and stimulation was provided for every child. Those who had assessment at least twice, (at entry and after 1 year age) were included for this study. Results: Male were predominating (66.7%). Mean age was 18 and 19 days on the 1st ; 17 and18 months on last assessment day in case and control group respectively. NDI was identified in 89% and 35% in case and control group respectively. On last assessment, 42% developed disability (permanent functional deficit), 35.8% achieved age appropriate developmental skills, 20% were lost to follow up, and 2 children died among the case group. These were 16% (13/81), 72% and 12% respectively among the control group. Significant correlation was found between the 1st and last assessment result among the case and control group. Conclusion: Early identification of NDI using a valid assessment tool and immediate intervention could probably reduce the disability in babies with HIE. A long time evaluation of this cohort would provide valuable information. Bangladesh J Child Health 2015; VOL 39 (1) :6-13